The Oxford handbook of public choice. Volume 1 - Congleton, Roger D.; Grofman, Bernard; Voigt, Stefan (Oxford handbooks online., 2019)
The two volume Oxford Handbook of Public Choice provides a comprehensive overview of the Public Choice literature. Volume 1 covers rational choice models of elections, interest groups, rent seeking, and public choice contributions to normative political economy. It begins with introductory chapters on rational choice politics, the founding of public choice, and the evaluation and selection of constitutions.